PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN HOTEL CAMPLONG SAMPANG - Abdul Jamali; Syaiful Syaiful (Universitas Methodist Indonesia, 2020)
This study aims to determine the effect of compensation and work environment as independent variables both simultaneously and partially on employee performance and the dominant variable between the two variables. This type of research is quantitative descriptive using multiple linear regression analysis. The data collection used a questionnaire with a sample of 47 employees of the Camplong Hotel in Sampang district. The results of this study are seen from the t-test with a probability of 0.05 having a sig. X1 is 0.000 and the value is sig. X2 is 0.003 where the value is less than Alpha 5%. It means that both independent variables partially and simultaneously affect employee performance. Finally, compensation is the most dominant variable affecting employee performance.